Salient Conclusive Remarks on Epidemiology and Clinical Manifestations of Pediatric COVID-19: Narrative Review - Abdelwahid Saeed Ali; Ahmed Mossa Al-Hakami; Ayed Abdullah Shati; Ali Alsuheel Asseri; Saleh Mohammed Al-Qahatani (Frontiers Media S.A., 2020)
The ongoing pandemic of COVID-19, which is caused by the novel coronavirus named severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), constituted significant public health concerns and impacted the human populations with massive economic and social burdens worldwide. The disease is known to infect people of all ages, including children, adults, and the elderly. Although several reports about pediatric COVID-19 were seen in the literature, we believe that the epidemiology and pathology of the infection described in these reports are not conclusive. Therefore, in this scientific communication, a narrative review study was performed to shed some light on the characteristic epidemiological features and clinical phenotypes of pediatric COVID-19. In this report, we had compiled and presented the different epidemiological features of the disease related to the age of infection, virus acquisition, explanations of the low infectivity rates, and consequences of infections. The discriminatory clinical manifestations of the disease in children were also addressed and discussed in this review. The search included the data published from the date of the start of the pandemic in December 2019 up to October 2020. Our literature search revealed that children of all ages, including neonates, had been infected by the virus. Despite the fact that pediatric COVID-19 is less common to occur, as compared to the disease in adults, the infected children usually manifest the disease symptomatology in benign form. Asymptomatic and symptomatic adult patients are the primary source of the virus to the children. Intrauterine transmission of the virus and breastfeeding infections to the neonates were hypothesized in some studies but ruled out since they were not confirmed. Intensive review and discussion warranting the low infection rates and benign conditions of COVID-19 in children were also made in this study. As documented in many studies, the infectivity, morbidity, and mortality rates of the disease among the children populations are much lower than those in adults. They also seem to be lower than those observed during SARS-CoV and MERS-CoV epidemics. The described clinical phenotypes of COVID-19 in children do not differ much from those of adults, and complications of the disease seem to be associated with comorbidities.